An Evaluation of International Tourist’s Expectations and Experiences of the Coffee Festival of Buon Ma Thuot City, Vietnam - NIEM, Le Duc; ANH, Le Viet; DUYEN, Ha Thi Kim (Journal of Environmental Management and Tourism; Vol 12 No 6 (2021): JEMT Volume XII Issue 6(54) Fall 2021DO - 10.14505//jemt.12.6(54).20, 2021)
This paper employed the HOLSAT model to measure the expectations and experiences of tourists who came to the Buon Ma Thuot Coffee Festival (BCF) in Buon Ma Thuot City, Dak Lak Province of Vietnam. We asked 160 international tourists participating in the BCF to rate their expectations before the BCF and their experiences after/during the BCF. The analysis revealed mixed results. Although most positive attribute items (18 out of 26 attributes) met or exceeded tourists' expectations, tourists were very dissatisfied with the other 8 positive and 8 negative attribute items, especially those regarding environment protection, public services, infrastructures, and the BCF organization. Therefore, we suggest that the BCF strategy should be revised by considering the tourists' benefits. In addition, measures should be taken to maintain or enhance the positive attributes and tackle environmental problems and public service issues in the organization of the BCF.